Effect of Intervention in Subjects with High Risk of Diabetes Mellitus in Pakistan - Muhammad Zafar Iqbal Hydrie; Abdul Basit; A. Samad Shera; Akhtar Hussain (Journal of Nutrition and Metabolism)
Aims. To observe the rate of conversion from impaired glucose tolerance (IGT) to diabetes following lifestyle modification (LSM) or a combination of lifestyle and metformin compared to a control population with 18-month followup. Methods. Forty screening camps were organized, which 5000 people attended. Around 2300 persons filled the questionnaire and 1825 subjects were identified as high risk. Of 1739 subjects who took the oral glucose tolerance test, 317 subjects were identified as IGT. The 317 IGT subjects were randomized into three groups: control group was given standard medical advice, LSM group was given intensive lifestyle modification advice, while LSM + drug group was given intensive lifestyle advice and metformin 500 mg twice daily. Results. At the end, 273 subjects completed the study, giving a compliance rate of 86%. Total of 47 incident cases of diabetes were diagnosed (overall incidence was 4 cases per 1000 person-months with the incidence of 8.6 cases in control group, 2.5 cases in the LSM, and 2.3 cases in the LSM + drug groups). Conclusions. Study showed that lifestyle intervention had a major impact in preventing diabetes among IGT subjects in this region. Adding drug did not show any improved results. We recommend lifestyle advice and followup should be incorporated in primary health care.